Sellar Chordoma Presenting as Pseudo-macroprolactinoma with Unilateral Third Cranial Nerve Palsy - Wang, Hai-feng; Ma, Hong-xi; Ma, Cheng-yuan; Luo, Yi-nan; Ge, Peng-fei (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
We described a 61-year-old female with a sellar chordoma, which presented as pseudo-macroprolactinoma with unilateral third cranial nerve palsy. Physical examination revealed that her right upper lid could not be raised by itself, right eyeball movement limited to the abduction direction, right pupil dilated to 4.5 mm with negative reaction to light, and hemianopsia in bitemporal sides. CT scanning showed a hyperdense lesion at sellar region without bone destruction. Magnetic resonance imaging (MRI) revealed the tumor was 2.3 cm×1.8 cm×2.6 cm, with iso-intensity on T1WI, hyper-intensity on T2WI and heterogeneous enhancement on contrast imaging. Endocrine examination showed her serum prolactin level increased to 1,031.49 mIU/ml. The tumor was sub-totally resected via pterional craniotomy under microscope and was histologically proven to be a chordoma. Postoperatively, she recovered uneventfully but ptosis and hemianopsia remained at the 6th month.